The google classroom online learning platform the use analysis for biology students - Dini Aisyah Rangkuti; Syarifah Widya Ulfa (JPBIO (Jurnal Pendidikan Biologi), 2022)
The Covid-19 virus epidemic that is still spreading throughout the world has caused a shift in the learning process, where previous interactions occurred face-to-face, and then the interaction switched through the help of a platform. This study examines the experience of using Google Classroom for biology learning media in eleventh grade during the Covid-19 virus outbreak. This research takes place from December 2021 to March 2022. This type of research is descriptive quantitative. The population of this study was sampled using proportional random sampling. This study involved 45 students in the eleventh grade majoring in natural science at State Senior High School 1, Kotanopan. Data was collected through questionnaires and documents. A closed questionnaire with 45 validated and distributed items were used to collect data. Technical analysis of the data used descriptive quantitative. Based on the research, the following are the results of the analysis of the use of Google Classroom for biology in eleventh grade: 1) Overall, the experience of using Google Classroom as a means of learning biology is excellent, with a score of 81.48%. 2) A study of the factors supporting the adoption of Google Classroom as a biology learning platform was good, with 66.22%. 3) The study of the barriers to adopting Google Classroom as a biology learning platform was hampered by 33.2%. During the Covid-19 virus outbreak, online biology learning through Google Classroom can complement classroom teaching.